2017
DOI: 10.1111/myc.12724
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole liquid vs tablet formulation in lung transplant recipients

Abstract: Posaconazole is an extended-spectrum triazole antifungal used in the treatment and prophylaxis of Aspergillus infections. It is available as oral suspension (POS-Liq) and delayed-release tablets (POS-Tab). The aim of this longitudinal, retrospective study was to compare the clinical effectiveness, toxicity and pharmacokinetics of POS-Liq vs POS-Tab in lung transplant recipients (LTx-recipients), who were treated with both formulations subsequently. Twenty-four consecutive LTx-recipients with 191 documented pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 37 publications
(85 reference statements)
0
35
0
Order By: Relevance
“…2 and 3), the difference was small and neither clinically relevant nor statistically significantly different, suggesting that the variability of POS-tab C min is still as large as that of POS-susp C min (20). Aside from one study, which reported lower POS C min variability with the tablet regimen in 24 lung-transplant patients (8), such a comparison of the intra-and interpatient variability of POS C min between the two oral galenic formulations of POS has never been performed. Several studies reported CVs for the POS-tab C min , but comparing CV values is problematic since calculation methods of CV differ.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2 and 3), the difference was small and neither clinically relevant nor statistically significantly different, suggesting that the variability of POS-tab C min is still as large as that of POS-susp C min (20). Aside from one study, which reported lower POS C min variability with the tablet regimen in 24 lung-transplant patients (8), such a comparison of the intra-and interpatient variability of POS C min between the two oral galenic formulations of POS has never been performed. Several studies reported CVs for the POS-tab C min , but comparing CV values is problematic since calculation methods of CV differ.…”
Section: Discussionmentioning
confidence: 86%
“…However, although the variability of the POS-susp trough concentrations (C min ) is known to be significant, with interindividual and within-subject coefficients of variation (CV) as high as 64% and 49%, respectively (7), little is known about the variability of the POS-tab C min . A recent crossover study showed lower within-subject CV for the POS-tab C min in lung-transplant patients treated with POS-susp and then with POS-tab (8). However, the number of patients was quite low (n ϭ 24), and interindividual CVs were not studied.…”
mentioning
confidence: 96%
“…Prior studies have demonstrated the tolerability and effectiveness of short-term PS prophylaxis. 12,13 Our data showed that patients on PS had fewer disruptions or changes in AF prophylaxis. Medication sustainability is important with AF prophylaxis as medication alterations require dose adjustments in anti-rejection medications requiring close monitoring.…”
Section: Discussionmentioning
confidence: 65%
“…Since PS is not a first‐line AF prophylactic agent at our institution, fewer patients were exposed to PS than IT or VR. Prior studies have demonstrated the tolerability and effectiveness of short‐term PS prophylaxis . Our data showed that patients on PS had fewer disruptions or changes in AF prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The new tablet formulation makes it possible to reach higher POS C min values than for the oral suspension [6][7][8]. This greater POS C min could theoretically result in a greater risk of side effects, although no study has yet clearly highlighted increased toxicity with the POS tablet formulation [2,[9][10][11][12][13][14]. Hence, no upper threshold for the POS C min has yet been proposed, even if some authors have suggested that dose reduction could be feasible for at least half of patients [15,16].…”
Section: Introductionmentioning
confidence: 99%